PENGEMBANGAN MODEL PERMAINAN KECIL BERBASIS COMPASSION UNTUK MENINGKATKAN SIKAP KEYAKINAN DIRI DAN KESIAPAN KERJA PESERTA DIDIK DI SMK - muchammad ali irfan (Jurnal Pedagogik Olahraga, 2025)
This study aims to develop a compassion-based small game model for extracurricular activities to improve self-efficacy and work readiness among vocational high school (SMK) students. The research employed a Research and Development approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects consisted of students from SMKN 2 Buduran for the small-group trial and SMKN 1 Sidoarjo for the large-group trial. Data were collected through observations, interviews, expert validation questionnaires, and pretests and posttests on the variables of self-efficacy and work readiness. The validation results indicated that the product fell into the “highly feasible” category, with a high level of practicality after revisions based on expert feedback. The paired sample t-test showed significant improvements in both the small-group trial (Sig. 0.000 and 0.006) and the large-group trial (Sig. 0.000 and 0.000), indicating that the compassion-based small game model is effective in enhancing students’ self-efficacy and work readiness. Therefore, this model is feasible to be implemented in vocational school extracurricular activities as an innovative character education approach and soft-skills reinforcement to support students’ readiness for the workforce Keyword: Small games, Compassion, Self-efficacy, Work readiness, Model development, Vocational high school students